The Effect of Music-Based Intervention on Linguistic Skills: A Systematic Review - Sinn, Ow Su; Hwa, Poon Chiew; Wing, Cheong Ku; Cooper, Shelly (Harmonia: Journal of Arts Research and Education, 2022)
Music-based approaches, including singing and movement, have received an extensive examination by researchers. Previous study results have revealed that music-based approaches improved young children’s music skills and enhanced social, linguistic, and logical thinking skills. This review characterizes and compares existing studies to investigate the use of music and movement to improve linguistic skills. This systematic review followed the SPIDER search tool by investigating the samplings (S), the phenomenon of interest (PI), design (D), evaluation (E), and research type (R). This systematic review includes studies published between 2001-2018 with participants ranging from 4 to 12 years old. The authors investigated the designs of 20 articles.